Sulfonamides and Penicillin Residue in Market Milk - Thapaliya, Manish; Karki, Tika B.; Sedai, Damodar (Journal of Food Science and Technology Nepal, 2014)
The present study was conducted at laboratory of Veterinary Standards and Drug Administration Office, Tripureshwor, Kathmandu in the month of October to December 2007 with aim of determining the prevalence and level of sulfonamide and penicillin residue semi-quantitatively in market milk samples from Kathmandu, Lalitpur, Bhaktapur and Kavrepalanchowk districts. All the samples were processed using standard procedure given in the protocol of the rapid residue test kit provided by the Division of Food, Department of Medical Sciences, Ministry of Public Health, Thailand. The prevalence of antibiotic residue was found to be 17.3% (n=26) of the total of 150 samples collected. Out of the total samples 12% (n=18) were found to contain penicillin residue and 5.3% (n=8) were found to contain sulfonamide residue. Sulfonamide residue was detected in the range of 0-1 ppb in 6 samples and 2-4 ppb in 2 samples. Similarly, penicillin residue was found in the range of 0-1 ppb in 14 of the samples and 2-4 pbb in 4 samples. The residues level detected were below their MRLs as set by the Codex Alimentarius Commission. The occurrence of the antibiotic residue in the tested milk samples was compared whether it differs from district to district. Statistically, there was no significant difference on the occurrence of the antibiotic residue in the tested milk from district to district. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11751 J. Food Sci. Technol. Nepal, Vol. 8 (60-64), 2013